Pengembangan Buku Penuntun Praktikum Sistem Peredaran Darah Manusia dengan Model Argument-Driven Inquiry (ADI) - Widya Hendriyani; Neni Hasnunidah; Berti Yolida (Bioedusiana: Jurnal Pendidikan Biologi, 2020)
This study aims to produce a practical guidebook of human circulatory system with Argument-Driven Inquiry (ADI) model for students at junior high schools. The design of this research was RD with 4-D model including define, design, develop, and disseminate. However, this research was only up to the develop step. The result of this study is in form of a practical guidebook of human circulatory system and using language that is easily understood and in accordance with EYD. Then, the practical worksheet consists of student identities, title of practices, basic theories, objectives, research questions, tools, materials, work steps, argumentation schemes, argumentation sessions, and reports. Next, the results of validation of experts and practitioners as well as the results of the readability test of the students obtain "Excellent" category. Moreover, the results of the implemented tests of all practices obtain "Almost All Activities Implemented" category. As a result, the practical guidebook of the human circulatory system with ADI model is valid and practical.